Craniofacial morphometric measurements of children with celiac disease - Işıkay, Şedat; Bahşi, İlhan; Orhan, Mustafa; Kul, Seval; Kızılkan, Neşe; Kocamaz, Halil; Şan, Murat (Kowsar Medical Publishing Company, 2020)
Objectives: To examine the craniofacial morphologic features of children with celiac disease and to investigate the presence of specific features in this disease. Methods: Totally 100 celiac patients between the ages of 3 and 17 years who were diagnosed with celiac disease by biopsy and 100 healthy age-and sex-matched children were included in the study. Photographs of the children were taken using a SLR digital camera by one and the same person at a natural head position. The parameters specified on the photograph were measured with ImageJ 1.50b software. Twenty eight landmarks were identified on the photos. Using these landmarks, 41 distances and 5 angles were measured. Thirty eight anthropometric ratios were calculated. Results: Twenty seven distances, 1 angle and 9 ratios were determined shorter; 3 distances, 2 angles and 7 ratios were determined larger in patients with celiac disease compared with the healthy individuals. These differences were statistically significant. Conclusions: There were significant alterations in some craniofacial morphometric parameters in children with celiac disease when compared with healthy controls. However, since the data is limited, a clear conclusion could not be achieved about a morphological feature directly associated with celiac disease in children. Further prospective studies with longer follow-up periods are warranted to determine the effects of celiac disease on craniofacial morphological measurements.
Keywords: Celiac Disease; Craniofacial Morphometry; Facial Analysis